2017
DOI: 10.1002/lary.26898
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between endolymphatic hydrops in the vestibule and low‐frequency air‐bone gaps

Abstract: 4. Laryngoscope, 128:1658-1662, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…It has already been shown that some cases of endolymphatic hydrops can mimic the TW syndrome with a similar clinical presentation ( 49 52 ). Besides, primary overpressure in the endolymphatic or perilymphatic spaces could explain a limited conductive hearing loss as previously reported ( 53 – 55 ). It is worth adding here that the notion of “inner ear conductive hearing loss,” considered lately as specific to TW lesions, was already used by Muchnik et al to describe the air bone gap (ABG) observed in some patients with Menière disease ( 53 ).…”
Section: Discussionsupporting
confidence: 59%
“…It has already been shown that some cases of endolymphatic hydrops can mimic the TW syndrome with a similar clinical presentation ( 49 52 ). Besides, primary overpressure in the endolymphatic or perilymphatic spaces could explain a limited conductive hearing loss as previously reported ( 53 – 55 ). It is worth adding here that the notion of “inner ear conductive hearing loss,” considered lately as specific to TW lesions, was already used by Muchnik et al to describe the air bone gap (ABG) observed in some patients with Menière disease ( 53 ).…”
Section: Discussionsupporting
confidence: 59%
“…12 First, audiograms of patients with MD showed unexplained air-bone gaps at low frequencies from 13% to 32% in the literature, even though no middle ear pathology could be demonstrated. 13,14 In addition, some methodologic differences between our study and the aforementioned study 12 should be stated to understand why the results are in disagreement. The authors of this study enrolled not only patients with MD (66% of the total) but also patients with other otologic disorders who presented with severe hydrops according to the Nakashima score.…”
Section: Discussionmentioning
confidence: 96%
“…The significant LFABG was defined to be greater than average 15 dB at 250, 500, and 1 kHz. The definition of LFABG has been reported in some of the Meniere disease research [ 16 , 17 ], but it was the first time covered in PLF research. VNG was tested for identifying the spontaneous and positional nystagmus.…”
Section: Methodsmentioning
confidence: 99%